Mastitis-associated production of S100A10 in the mammary gland of goats - Jaisue, Jirapat; Liang, Zi-Long; Marufah, Nur Laili; Tsugami, Yusaku; Nii, Takahiro; Isobe, Naoki (Frontiers in Animal Science, 2026)
Mastitis is the most common inflammatory disease of the mammary gland in dairy ruminants and remains a major challenge in the dairy industry. S100A10 is a calcium-binding protein involved in plasmin generation and immune regulation, however, its relationship with mammary inflammation has not been fully clarified. This study investigated the production of S100A10 in the mammary glands of goats as a ruminant model and quantified temporal changes in its milk concentration following intramammary lipopolysaccharide (LPS) infusion. Milk S100A10 concentrations were measured by ELISA, while S100A10 and plasmin-related gene expressions in milk somatic cells (SCs) were analyzed using RT-PCR. Localization of S100A10 in mammary tissue and milk leukocytes was assessed through immunohistochemistry and immunocytochemistry. S100A10-positive cells were identified in macrophages and neutrophils in both milk and mammary tissue. Intramammary LPS infusion markedly increased S100A10 secretion into milk compared with pre-infusion levels. Moreover, the expression of plasminogen activator–related genes (PLAU and PLAUR) in milk SCs increased significantly after LPS infusion. These findings indicate that S100A10 is produced within the mammary gland and that its production is closely associated with inflammatory responses and plasmin generation.